1978
DOI: 10.1136/bjo.62.12.843
|View full text |Cite
|
Sign up to set email alerts
|

Acute follicular conjunctivitis and keratoconjunctivitis due to herpes simplex virus in London.

Abstract: This report presents the findings in 25 cases of acute herpetic follicular conjunctivitis which presented without characteristic lid, face, or corneal signs of herpetic infections. In most of them, the correct diagnosis could be made only by cultural or serological tests for HSV infection. Methods and patientsPatients with acute follicular conjunctivitis or keratoconjunctivitis without facial, lid, or corneal lesions typical of HSV infection at the first visit, but with positive cultural or serological tests f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…This finding confirms a previous report that HSV can cause AC. 22 In this study serological evidence of active HSV infection (HSV-IgG antibodies at level of 1/128 or higher in blood or at a level of 1/8 or higher in tears) was found in 16 patients. HSV was not isolated from these patients, and we were unable to find clinical or laboratory evidence of bacterial, CT, or AV infection or allergy.…”
Section: 20mentioning
confidence: 51%
“…This finding confirms a previous report that HSV can cause AC. 22 In this study serological evidence of active HSV infection (HSV-IgG antibodies at level of 1/128 or higher in blood or at a level of 1/8 or higher in tears) was found in 16 patients. HSV was not isolated from these patients, and we were unable to find clinical or laboratory evidence of bacterial, CT, or AV infection or allergy.…”
Section: 20mentioning
confidence: 51%
“…Hence, these conditions may remain largely unrecognised, and treated unnecessarily with anti-0 1a 2 3 As 2 -wt35 gye.…”
Section: Discussionmentioning
confidence: 99%
“…Primary ocular infection may present as an acute follicular conjunctivitis or keratoconjunctivitis with or without characteristic lid or corneal lesions. 2 In recent years we have observed changes in the epidemiological and clinical features of primary HSV ocular infection in patients attending the External Eye Diseases Clinic at Moorfields Eye Hospital. In this report we present the major features of primary HSV ocular infection observed in 108 patients and compare these with the features of the disease reported previously.…”
mentioning
confidence: 99%
“…Clinical manifestations of primary ocular HSV-1 infections tend to manifest in youths or young adults. Long term studies of ocular HSV-1 in the United States and Britain found the mean age for the first occurrence to be 37.4 years of age and 25 years of age respectively (Darougar et al, 1978; Liesegang, 1988, 1989). The annual incidence of all types of new ocular HSV infections has recently been estimated at 11.8 per 100,000 people in the United States (Young et al, 2010), similar to the incidence of 8.4 per 100,000 people found over two decades ago in a similar population (Liesegang et al, 1989).…”
Section: Herpetic Infectionmentioning
confidence: 99%